2016
DOI: 10.5688/ajpe80588
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Effects of Continuing Education Programs on Providing Clinical Community Pharmacy Services

Abstract: Objective. To summarize the effects of media methods used in continuing education (CE) programs on providing clinical community pharmacy services and the methods used to evaluate the effectiveness of these programs. Methods. A systematic review was performed using Medline, SciELO, and Scopus databases. The timeline of the search was 1990 to 2013. Searches were conducted in English, Portuguese, and Spanish. Results. Nineteen articles of 3990 were included. Fourteen studies used only one media method, and the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
33
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 40 publications
0
33
0
1
Order By: Relevance
“…Increasingly, more countries worldwide are implementing CE program for community pharmacists as obligatory lifelong learning programs in an attempt to improve clinical community pharmacy services [7]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasingly, more countries worldwide are implementing CE program for community pharmacists as obligatory lifelong learning programs in an attempt to improve clinical community pharmacy services [7]. …”
Section: Introductionmentioning
confidence: 99%
“…In the nation there is a shift in trend of pharmacy practice towards patient-focused one [9]. Such shift is known to create a need to develop and maintain expertise and competence in new areas, including pharmacotherapy and interpersonal communication among others [7]. …”
Section: Introductionmentioning
confidence: 99%
“…8,9 Specific to the pharmacy profession, studies analyzing individual CPE activities have generally, although not exclusively, shown positive effects on behaviors or patient outcomes, [10][11][12][13][14][15][16] and one systematic review cited the effectiveness of the majority of CPE programs based on their reported outcomes measures, most often knowledge or skill modification. 17 Given the frequency of evidence supporting continuing education outcomes, the ultimate CE research question is not "Is CE effective?" but rather "What kinds of CE are effective?"…”
Section: Introductionmentioning
confidence: 99%
“…Most studies were oriented to the effect of continuing education programs in modifying the understanding and skills of pharmacists, and only one study evaluated the benefits of the program for patients or customers. The authors concluded that there is not enough evidence to support which media methods are the most effective and that it is needed to intervene with robust, standardized and validated methods (8). Then, some challenges are still dormant, among them there are programs of continuing education, evaluation and continued implementation, which have innovative approaches supported by ICT and that are oriented at the outpatient pharmacies in the Colombian context with the purpose of achieve an interdisciplinary work.…”
mentioning
confidence: 99%
“…educative programs for outpatient pharmacists as obligatory and lifelong learning programs to improve pharmacy care services (8).…”
mentioning
confidence: 99%